Greek Myth and Religion : Collected papers. - Henrichs, Albert, 1942-2017 (Collected Papers, 2019)
This volume contains the collected papers of Albert Henrichs on numerous subjects in ancient Greek myth and religion. What was ancient Greek religion really like? What is the reality of belief and action that lies behind the unwieldy sources, which stem from vast areas and epochs of the ancient world? What is the meaning, intended and otherwise, of religious action and speech in ancient Greece? Who were the Greek gods, how were they worshipped, and how were they viewed by those who worshipped them? One of the leading students of ancient Greek religion over the past five decades, Albert Henrichs, the Eliot Professor of Greek Literature at Harvard University, combines wide and deep learning, a pragmatic, incisive approach to the sources, and an apt use of comparative perspectives. Henrichs breaks new ground in discussing sacrifice, libation, cultic identity, religious action and speech, epiphany, and the personalities of the gods. Special attention is devoted to ancient Greek sources on the ancient Persian prophet Mani, founder of Manichaeism. As a group, Albert Henrichs' papers on Greek religion offer a basic education on Greek myth and religion and constitute a blueprint for serious study of the subject